A STUDY ON THE IMPACT OF ONLINE LEARNING ON THE EMPLOYABILITY SKILLS OF ENGINEERING STUDENTS (International Journal of Food and Nutritional Sciences, 2022)
Online getting-to-know technologies are at the forefront of new advanced academic technologies. Online Learning is a shape of education that is increasingly used in faculties in the evolved global. The utilization of Online Learning has been considered at an initial degree for the past few years, but now it's faced an enormous boom everywhere in the world because of COVID-19 pandemic state. In this paper, a strive has been made to look at the effect of online Learning on the employability skill of engineering college students within the Tamil Nadu region.